BILINGUALISM AMONG THE ADOLESCENTS IN BADUNG REGENCY, BALI - Muliana, I Nyoman; Suastra, I Made; Budiarsa, Made; Dhanawaty, Ni Made (e-Journal of Linguistics, 2015)
This paper presents a discussion of bilingualism among the adolescents in Badung Regency, the Province of Bali. It aims to explore the bilingualism situation and the existence of Balinese Language among them. The discussion is based on participant observation to the adolescents and it is based on Sociolinguistic Theory. The result of the discussion shows that the adolescents in Badung Regency are bilinguals of Balinese and Indonesian languages. They use Balinese language in all their communicative activities, except some females occasionally showed the use of Indonesian language. Their conversations both in Balinese and Indonesian languages are also followed by code mixing of the words and phrase of Indonesian, Balinese, and English languages.  The result of the discussion also indicates that Balinese language still used and maintained by the adolescents in Badung Regency.
Keywords: Bilingualism, Adolescents, Badung Regency